THE CORRELATION BETWEEN GRAMMATICAL COMPETENCE AND STUDENTS' ABILITY IN WRITING ENGLISH TEXT AT THE ELEVENTH GRADE OF SMAN 9 KOTA JAMBI - Meivita, Dewi; Fitri, Nurul; Munawwaroh, Khidayatul (JELT: Journal of English Language Teaching, 2025)
This research aimed to investigate the correlation between grammatical competence and English text writing ability among eleventh-grade students at SMAN 9 Kota Jambi. This research was quantitative with a correlational approach. The subjects of the research were 36 eleventh-grade students at SMAN 9 Kota Jambi in Academic Year 2023/2024. The techniques of collecting data were a grammar test and a writing test. The research used the Pearson product-moment correlation coefficient to analyze the data. The results of the research show that there is a very low positive correlation (r = 0.166) between students' grammatical competence and their ability in writing English texts. This correlation is not statistically significant at both 5% and 1% levels. The findings indicate that 11.11% of students had excellent performance in the grammar test, while 16.67% showed very good performance in the writing test. The study concludes that there is no significant correlation between students' grammatical competence and their ability in writing English texts.